1982
DOI: 10.1007/bf01421298
|View full text |Cite
|
Sign up to set email alerts
|

Correlations between fission fragments and light charged-particles in the reaction20Ne+197Au at 13 MeV/nucleon

Abstract: Energy of light charged-particles has been measured in coincidence with one or two fission fragments in the reaction Z°Ne+ 197Au at a bombarding energy of 13 MeV/u. The fission cross section was found equal to 1,340 + 260 rob. Assuming that it represents the totality of the fusion cross section, the critical value l c is deduced equal to 93 _+ 9 h, higher than /By=o--74 in the rotating liquid drop model. The main emission source for protons and alpha particles seems to be a thermally equilibrated composite sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

1983
1983
1986
1986

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 26 publications
1
3
0
Order By: Relevance
“…For reactions of 3t5 MeV 160 and 340MeV 4~ with 238U, similar observations have been made via measurements of 4He production in coincidence with fission fragments of known fold angle [34,38,96 and references therein]. Production of #He in the backward hemisphere was found to be predominantly associated with essentially full momentum transfer to the fissile nucleus, The reaction 265MeV 2~ has also been studied by Rivet et al [46] who arrive at similar conclusions. Several studies of similar reactions have reported that forward-angle inclusive spectra can be parameterized by an isotropic emission source moving at one-half to two-thirds of the projectile velocity vp.…”
Section: Experimental Techniquessupporting
confidence: 63%
See 1 more Smart Citation
“…For reactions of 3t5 MeV 160 and 340MeV 4~ with 238U, similar observations have been made via measurements of 4He production in coincidence with fission fragments of known fold angle [34,38,96 and references therein]. Production of #He in the backward hemisphere was found to be predominantly associated with essentially full momentum transfer to the fissile nucleus, The reaction 265MeV 2~ has also been studied by Rivet et al [46] who arrive at similar conclusions. Several studies of similar reactions have reported that forward-angle inclusive spectra can be parameterized by an isotropic emission source moving at one-half to two-thirds of the projectile velocity vp.…”
Section: Experimental Techniquessupporting
confidence: 63%
“…No. 1, F-91406 Orsay, France ration of fission-like fragments [38,46,[63][64][65][95][96][97]. The nearly isotropic component is particularly interesting for heavy nuclei as it offers a possible probe of the time evolution of the composite nucleus in its course toward fission-like breakup [64,[96][97][98].…”
Section: Introductionmentioning
confidence: 98%
“…The first clue to such a comportment can even be found in light particle induced reactions on heavy targets [1,4]. Extensive studies of charged particle emission in heavy-ion reactions [7][8][9][10][11][12][13][14][15][16][17]19] have fully confirmed the existence of this anomalous type of evaporation and precised its characteristics as functions of excitation energy and spin, see e.g. Ref.…”
Section: Introductionmentioning
confidence: 82%
“…In principle, the simultaneous measurement of the fission fragment folding angle in case of fissile heavy residues may provide analogue information. However, an experiment of this type by Rivet et al [31] on the same reaction as studied here did not cover the interesting range of e-particle emission angles below 50 ~ For the system 310MeV 160AFZ38u studied by…”
mentioning
confidence: 99%